Evaluation of the Proline Content in Tissues of Soybean (Glycine max [L.] Merr.) DT26 Cultivar During Salt Acclimation - Mai, Le Quynh; Hang, Ha Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 32 No 1S, 2016)
Abstract: Salinity is one of the abiotic stresses that reduces the growth and development of plant. Soybean ( Glycine max [L.] Merr.) is known to be sensitive to salinity; not only agronomy traits but also nodulation of soybean plant are inhibited in high salt concentration, thus reduce the yield of soybean. To cope with salt stress, soybean has developed several tolerance mechanisms. One of those is accumulation of comparative solutes which induce high osmotic potential for plant cells. Proline considered as a comparative solute was reported to play a critical role in increasing salt tolerance. However,  knowledge about salt acclimation, the phenomenon of increase salt tolerance after exposing to salt stress at lower level before, are limited. Here, the changes of proline during salt acclimation in germination stage of soybean DT26 variety were studied. Proline content of salt acclimation and non-acclimation samples were compared to find out the role of acclimation in inducing salt tolerance in soybean through accumulation of proline. The results indicated the actually enhancement of proline biosynthesis during salt acclimation but it really differed from tissue to tissue of soybean plant. Keywords: Proline, salt acclimation, salt tolerance, soybean, Glycine max , DT26.